Pengaruh pendidik yang berkualitas terhadap mutu pendidikan di perguruan tinggi - Misa Dasmi; Mila Darti; Wira Yuliyasta (PT. Hasba Edukasi Mandiri, 2025)
Educators are one of the important factors that determine the quality of education in higher education institutions. Qualified educators can influence the quality of education because they are able to deliver learning materials clearly and in an easily understandable manner. In addition, high-quality educators are better able to adapt teaching methods to the needs of their students. Students who are taught by qualified educators tend to have higher satisfaction with the teaching and learning process. Therefore, higher education institutions must make continuous efforts to improve the quality of their teaching staff, as qualified educators have a significant impact on student learning outcomes. This study aims to analyze the effect of educator quality on the quality of education in higher education. The research employed a quantitative method, using questionnaires as the data collection technique through Google Forms, which were distributed across different levels of education. The results of this study indicate that educator quality has a positive effect on the quality of higher education. Qualified educators also play an important role in creating a conducive academic environment for learning, inspiring students, and serving as role models in the development of students’ intellectual abilities and character. The conclusion of this study shows that qualified educators have an essential role in improving the quality of higher education. Educators not only provide in-depth knowledge but are also able to inspire, guide, and motivate students. With the support of qualified educators, higher education institutions can achieve higher educational standards and produce graduates who are ready to compete in the workforce. The limitation of this study is that the research was conducted only in several universities in West Sumatra. Future researchers are expected to conduct similar studies in various universities to further extend and develop this research.